The effect of changing the formation of multiple input multiple output antennas on the gain - Majed Omar Dwairi; Mohamed Salaheldeen Soliman; Amjad Yousef Hendi; Ziad AL-Qadi (Institute of Advanced Engineering and Science, 2023)
In this paper, different 2×1 and 2×2 multiple input multiple output (MIMO) antennas were investigated with changing substrate shapes and changing the placing of the patches on the substrate, all the investigated antennas based on FR-4 substrate are characterized by , and loss , with a partial ground. The original antenna covered 3.4 to 13.5 GHz. The best simulation results of the proposed 2×1 MIMO antenna received for 2×1 inverted with high ultra-wideband (UWB) with bandwidth up to 40 GHz, the received maximum gain was up to 6.51 dB, with an average gain of more than the original single antenna at about +1.27 dB. The best of eight 2×2 MIMO antennas configurations that give good results were shown. The best-received gain compared with a single antenna gain were at 4.2 GHz about +2.73, +1.17, and +0.92 dB for plus-shaped, loop, and chair-shaped respectively. A comparison between the proposed MIMO antennas and other reported works were done. The proposed MIMO antennas give a good maximum gain and are suitable for different narrow bands within the UWB such as wireless local area network (WLAN), worldwide interoperability for microwave access (WiMAX), aeronautical radio navigation (ARN), International Telecommunication Union 8-GHz (ITU-8), and X-Band applications with the ability to give high gain without the need to increase the radiated power of the transmitter antenna.